Kepentingan Nasional Tiongkok Bekerjasama dengan Iran di Bawah Kesepakatan Sanksi Kepemilikan Nuklir Joint Comprehensive Plan of Action - Silviana Iskandar (Journal of International Relations Diponegoro, 2023)
China still intends to work with Iran despite the restrictions placed on it as a result of the nuclear deal or the Joint Comprehensive Plan of Action (JCPOA). More than three decades of cooperation between China and Iran have improved the two nations' mutually beneficial relationship. Iran also holds a significant position for China as a supplier of oil and energy. This study employs qualitative research techniques for descriptive analysis and discovers that China's national interests, particularly in the economic and security sectors against Iran stands, are the reason why China continues to cooperate with Iran despite being subject to the JCPOA's sanction provisions. China has a national interest in the Iranian state in this sense, despite the JCPOA's sanctions against Iran. Iran sees China as a partner for long-term economic cooperation in the sector of energy exports since China is a nation that depends on oil exports as a source of revenue. This study examines China's foreign policy toward Iran, which is subject to the JCPOA's nuclear property sanctions, using a national interest framework.